Analisa Aliran Daya pada Sistem Tenaga Listrik menggunakan ETAP 12.6 - Al-afifi, Umar Faruq (Teknik Elektro Universitas Lancang Kuning, 2021)
Analysis of load flow in the Electric Power System is needed with the aim of improving and optimizing the system. This analysis can be carried out in various stages, either manually or with computer applications. Etap is one application that can be a tool for the analysis. Modeling the electric power system with ETAP Power Station 12.6 begins with analyzing the state of the system and then proceeds with Analysis and Actions to improve the state of the system. The advantage of simulation with ETAP Power Station 12.6 is that it can use 100% load. This research was conducted by utilizing ETAP Power Station 12.6 as a simulation medium with an electric power system that has 20 buses. In this study using a power source in the form of a power grid or substation with a total capacity of 100 MVA. The data used for the analysis is using One Line Diagram, Channel Data and Load Data. Based on these data, a research was conducted using ETAP Power Station 12.6 for the study of power flow.